Protective effects of dammarane-type triterpenes from hydrolyzate of Gynostemma pentaphyllum against H2O2-induced injury and anti-hepatic fibrosis activities. (June 2018) - Zhang, Xiaoshu; Shi, Guohui; Liu, Mingbing; Chen, Rong; Wu, Xiaojun; Zhao, Yuqing
Graphical abstract: Three previously undescribed triterpenes were isolated from the hydrolyzate of total Gynostemma pentaphyllum saponins . Highlights: Three previously undescribed triterpenes were discovered from hydrolyzate of G. pentaphyllum . These triterpenes displayed more significant anti-hepatic fibrosis activity than positive control Silymarin. All the compounds exhibited excellent increased the ratio of viability of H9c2 induced by H2 O2 . Abstract: Gynostemma pentaphyllum (Thunb.) Makino is a kind of health food, and it is also used as a traditional medicine in Asia. In this study, phytochemical investigation of hydrolyzate of total G. pentaphyllum saponins led to the isolation of three previously undescribed triterpenes, Gypensapogenin R (1 ), Gypensapogenin S (2 ), and Gypensapogenin T (3 ). Their structures were mainly identified by 1D, 2D-NMR and HR-ESI–MS evidences. Anti-hepatic fibrosis activity was determined and the data showed that2 and3 exhibited more potent inhibitory effects (IC50 values 14.93 and 29.19, respectively) on the growth of t-HSC/Cl-6 cells than Silymarin (positive control), while having much weaker effect in the growth of normal cell. Additionally, all the compounds exhibited excellent increased the ratio of viability of H9c2 induced by H2 O2 . Here in we report isolation, structure elucidation, as well as the evaluation of the anti-hepatic fibrosis and cardiomyocytes oxidative injury activities of these three compounds.